«WHAT A WONDERFUL SONG! AND JUST – A HUMAN LIFE ...»: FOLK PARADIGM OF CREATIVITY OLGA FESENKO - Атрошенко, Г. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is devoted to the problem of author’s individual style by Olga Fesenko The complex mechanism of the functioning of folklore units in artistic texts is explored. The specificity of the artistic text and peculiarity of the individual-authorial style of Olga Fesenko at the language-linguistic level is considered. The visual and occasional folklorisms in the aspect of contextual realization is analyzed. On the material of the works the research of the folklore paradigm of creativity Olga Fesenko was proposed. It is emphasized on the artistic and cognitive value of poetry, due to the romantic elevation, folk poetic traditions in creativity.